A methyltransferase essential for the methoxypyrazine‐derived flavour of wine. (21st May 2013) - Dunlevy, Jake D.; Dennis, Eric G.; Soole, Kathleen L.; Perkins, Michael V.; Davies, Christopher; Boss, Paul K.
Summary: Methoxypyrazines are a family of potent volatile compounds of diverse biological significance. They are used by insects and plants in chemical defence, are present in many vegetables and fruit and, in particular, impart herbaceous/green/vegetal sensory attributes to wines of certain varieties, including Cabernet Sauvignon. While pathways for methoxypyrazine biosynthesis have been postulated, none of the steps have been confirmed genetically. We have used the F2 progeny of a cross between a rapid flowering grapevine dwarf mutant, which does not produce 3‐isobutyl‐2‐methoxypyrazine (IBMP), and Cabernet Sauvignon to identify the major locus responsible for accumulation of IBMP in unripe grape berries. Two candidate methyltransferase genes within the locus were identified and one was significantly associated with berry IBMP levels using association mapping. The enzyme encoded by this gene ( VvOMT3 ) has high affinity for hydroxypyrazine precursors of methoxypyrazines. The gene is not expressed in the fruit of Pinot varieties, which lack IBMP, but is expressed in Cabernet Sauvignon at the time of accumulation of IBMP in the fruit. The results suggest that VvOMT3 is responsible for the final step in methoxypyrazine synthesis in grape berries and is the major determinant of IBMP production.